2020
DOI: 10.1002/ejlt.201900332
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Origin of Commercial Flavored Rapeseed Oil by the Pattern of Volatile Compounds Obtained via GC–MS and Flash GC Electronic Nose

Abstract: Flavored rapeseed oil (FRO) is a typical hot‐pressed oil and is widely consumed in China due to its strong characteristic flavor and intensive color. In this study, volatile profiles of 33 representative commercial rapeseed oils in China are characterized by gas chromatography‐mass spectrometry (GC‐MS) and flash gas chromatography (GC) electronic nose system. 51 volatile compounds are identified and the nitriles (methallyl cyanide and 5‐cyano‐1‐pentene), aldehydes (nonanal, 3‐furaldehyde, and 5‐methyl‐2‐furanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 17 publications
0
27
0
1
Order By: Relevance
“…The oil chromatographic analysis identified a few or several dozen characteristic volatile compounds [ 35 ] present in the samples differing in the volume and constant surface of contact with oxygen and subjected to the 6-, 12-, and 18-h frying process determining the oil odour [ 36 ]. Table 2 presents the main volatile chemicals in the heat-treated oils and in the control sample as a function of retention time.…”
Section: Resultsmentioning
confidence: 99%
“…The oil chromatographic analysis identified a few or several dozen characteristic volatile compounds [ 35 ] present in the samples differing in the volume and constant surface of contact with oxygen and subjected to the 6-, 12-, and 18-h frying process determining the oil odour [ 36 ]. Table 2 presents the main volatile chemicals in the heat-treated oils and in the control sample as a function of retention time.…”
Section: Resultsmentioning
confidence: 99%
“…In the study of Zhang, Wu, et al. (2020), dimethyl sulfoxide was detected in 17 out of 33 commercial fragrant rapeseed oil samples, dimethyl trisulfide only in four oils, but neither dimethyl disulfide nor dimethyl sulfide was found in these oils. The distinction might be caused by various genetic types of rapeseed and the treatment conditions.…”
Section: Flavor Compounds In Rapeseed Oilmentioning
confidence: 93%
“…In a very recent study, Zhang, Wu, et al. (2020) found that glucosinolate degradation products were responsible for the pungent aroma and had a positive correlation with the erucic acid content. This finding might be related to the fact that rapeseed samples with a high erucic acid content (>3.0%) accounted for 92.5% of the whole samples in Sichuan, based on the “2018 National Rapeseed Harvest Quality Survey Report” in China.…”
Section: Flavor Compounds In Rapeseed Oilmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, many researchers have studied the flavor composition of rapeseed oil. Based on the flavor fingerprint, Gas chromatograph-Mass Spectrometry (GC-MS) technology has been proved suitable for vegetable oil category classification [6], origin identification [7], adulteration detection [8][9][10], processing flow control [11,12], as well as storage management [13]. These current studies mainly focused on the change of oxidation stability [14], quality indicators such as trace elements and aflatoxins of vegetable oil in the production process [15], and the optimization of process conditions [16,17].…”
Section: Introductionmentioning
confidence: 99%